2022
DOI: 10.1007/s40201-021-00780-0
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicity and bioremediation potential assessment of soil from oil refinery station area

Abstract: Purpose The aim of the present study was to evaluate the toxicity and biodegradation potential of oil hydrocarbons contaminated soil samples obtained from different depths at an oil refinery station area. An approach involving chemical, microbiological, respirometry and ecotoxicity assessment of soil polluted by oil hydrocarbons was adopted, in order to determine the biodegradability of pollutants and ecotoxicological effects of natural attenuation strategy. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Biotesting with garden cress is a sensitive method for the study of toxicants and is widely used in practice [6,7,[11][12][13][14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biotesting with garden cress is a sensitive method for the study of toxicants and is widely used in practice [6,7,[11][12][13][14].…”
Section: Resultsmentioning
confidence: 99%
“…Since most of the compounds in the composition of wet wipes are synthetic surfactants, the toxicity of which is known [4], high or extreme toxicity is manifested in wipes impregnated with these compounds. Currently, the need to review the compositions of wet wipes is considered from the angle of protection against microbial spoilage [14], and of rationalizing the physicochemical interactions between the fabric and the preservatives [15]. Attention should also be paid to the issues of the eco-friendliness of these materials [2,16].…”
Section: Resultsmentioning
confidence: 99%
“…The toxicity of the soil samples collected from the MWL was evaluated using the crustacean organism Heterocypris incongruens as the biotest organism. The test proved to be effective in assessing the quality of the environmental soil samples [ 53 ]. This test was employed to assess the ecotoxicity potential of the soil samples from the MWL, including the control soil samples and the reference samples standardized by ISO.…”
Section: Methodsmentioning
confidence: 99%
“…The eco-toxicity level of crude oil related pollutants in soil is of great concern to stakeholders (Ebulue, 2022). Pollutant's concentrations and the type of pollutants in topsoil can be characterized by analyzing chemically but when it comes to the overall soil quality, chemical analysis alone cannot reflect its true eco-toxicity level (Zawierucha et al, 2022). However, few studies have reported that biological methods seem to be more appropriate in determining the probable risk of pollutants in soil on the environment and its ecology (Tang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%